Crafting Unique Staycation Lodging Packages: Insights from Millennial Lifestyle Segmentation - Sherly Astuti; Marchela Indah Atrisia (TIJAB (The International Journal of Applied Business))
Background: In the post-pandemic landscape, the Tourism and Hospitality Industry, once a cornerstone of the Indonesian economy, experienced a significant downturn. This decline spurred the popularity of "staycations" as an alternative form of tourism among Indonesians. Understanding the perspectives of Indonesian millennial staycation travelers is essential for adapting to evolving travel trends and consumer preferences.